Antimicrobial Activities of Extracts and Flavonoid Glycosides of Corn Silk (Zea mays L) - Nessa, Fazilatun; Ismail, Zhari; Mohamed, Nornisah (International Journal of Biotechnology for Wellness Industries, 2012)
Corn silk refers to the stigmas of Zea mays L. (Gramineae) from the female flowers of maize. It is medicinally used in a number of diseases and contained a number of flavonoids. Screening of plants against pathogenic bacteria is an important step to validate its medicinal properties. Therefore, the aim of this study was to screen the antimicrobial activities of different solvent extracts, flavonoids of corn silk and compare the activities with standard antibiotic gentamycin. The pet-ether (PECS), chloroform (CECS) and methanol (MECS) extracts (25 mg/mL) of corn silk were tested for their antimicrobial activity. Twelve pathogenic bacteria such as Bacillus cereus, Bacillus subtilis, Staphylococcus aureus, Pseudomonas aeruginosa, Enterobacter aerogenase, Salmonella typhi, Salmonella paratyphi, Escherichia coli, Shigella sonneii, Shigella flexneri, Proteus vulgaris, Proteus mirabilis and one fungus Candida albicans were used to screen the extracts. Gentamycin (50 mg/mL) was used as reference antibiotic. Two isolated flavonoid glycosides (2.0 mg/mL) of corn silk were tested for their antimicrobial activity. The microbial growth inhibitory potential was determined by using the agar hole-plate diffusion method. PECS, MECS and flavonoids were sensitive against eleven bacteria out of twelve bacteria. CECS was sensitive only against five bacteria. No extracts and flavonoids were sensitive against Escherichia coli and Candid albicans. The results were compared with gentamycin, which was sensitive against all the bacteria tested. Extracts and flavonoids showed significantly (p<0.05) higher sensitivity against a number of bacteria than gentamycin.